(untitled) (Asian Journal of Medical and Biological Research, 2022)
ASD (Autism Spectrum Disorder) is a neuropsychiatric disorder with a hereditary component, and its prevalence in South Asia was assessed 1, out of every 93 children. Moreover, recent studies suggested that the etiology of autism is thought to be linked to anomalies in the synapse, where mutation or deletion of synaptic gene CNTNAP2 is responsible. Therefore, this research was aimed to find out specific signs and symptoms of ASD individuals as well as the distribution pattern of the CNTNAP2 allelic variant (rs7794745) as a genetic risk factor in the Bangladeshi population. A case-control study including an epidemiological survey to investigate the association and pathophysiology of CNTNAP2 (rs7794745) with ASD for the Bangladeshi population has been studied, where PCR-RFLP analysis and Sanger sequencing were used for 180 individuals (90 ASD samples and 90 healthy controls). Our retrieved data speculated a diverse clinical profile of ASD, in comparison to the control group (n=110); where 80.9% (p ≤0.001) of ASD patients (n =100) had severe social interaction difficulties, 50% (p ≤0.001) had language impairments, and 40.9% (p ≤0.001) had behavioral abnormalities. Furthermore, findings from Pearson’s chi-square test (p = 0.001) as well as logistic regression analysis of co-dominant (p = 0.0083), and recessive model (p = 0.0075) confirmed significant association between rs7794745 and in our studied sample. This research demonstrates the genetic variation of CNTNAP2 found in our studied population could open a new clue to identifying a reliable biomarker for early diagnosis of ASD though it is recommended that more study is needed with a larger group population. Asian J. Med. Biol. Res. 2022, 8 (2), 79-93